Fort Reliance, Yukon : An Archaeological Assessment - Clark, Donald W. (Donald Woodforde), 1932-2018 (Book collections on Project MUSE., 1995)
Initially founded by Francois Mercier as a small, semi-independent fur-trading post, Fort Reliance is of particular interest and importance because of its role in opening the Yukon to prospecting and mining, which eventually led to the Klondike discovery. The trading post became the primary focal point for what one author has termed the "Prelude to Bonanza." The location was also a pre-Gold Rush Han Athapaskan settlement, with a unique and somewhat enigmatic set of semisubterranean houses. Traces survive of the original structures, and possibly of all structures ever built there. This study describes the history of Fort Reliance, assesses the nature and extent of archaeological remains, and examines the relationship between Native use of the site, previously known through the recovery of stone artifacts that relate to a precontact or prehistoric technology, and the trading post